LEGISLATIVE RESTRICTIONS ON THE EXERCISE OF PROPERTY RIGHTS BY SPOUSES - Kozhevnikovа Victoria (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: the research is to identify and solve a set of theoretical and practical problems related to the laws of legal regulation of restrictions in the process of exercising property rights by spouses, improved concepts of modern understanding of restrictions on property rights of family relationships. Research methods: to achieve this goal, in the process of scientific research used a set of methods of scientific knowledge. General-scientific and special-scientific methods became the methodological basis of scientific work. Results: the provisions of the current family legislation of Ukraine on the normative procedure for establishing the limits of the exercise of subjective rights and restrictions in the right of joint joint ownership of spouses are clarified. Discussion: scientific approaches to the legal category of restrictions on the exercise of marital property rights are clarified. It is established that the husband and wife, exercising their rights, are guided by the limits established by law, the features of certain restrictions on the property rights of the subjects of family relations in the exercise of subjective rights are determined. It is outlined that the limits of family rights established in the current family law determine the proper conduct for each person, and restrictions reduce the possibility of exercising a particular right, apply to a certain (exclusive) range of subjects of individual family relationships established by the state, court decision, legal act in order to protect the rights and freedoms of other participants in family relations.